Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1177/112067210301300214
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Strabismus Fixus - A Case Report

Abstract: Strabismus fixus is a rare condition and usually is of convergent type in which one or both eyes are anchored in a position of extreme adduction. Convergent type strabismus fixus is considered to be a congenital disorder and a part of congenital extraocular muscle fibrosis syndrome. Villasecca and Martinez described an acquired type of strabismus fixus. Hayashi et al reported that progressive esotropia could develop into the acquired type of convergent strabismus fixus. There are very few reports of divergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In the current study, because most of the patients had full or nearly full ocular versions, the strabismus did not qualify as myopic divergent fixus variety, as has been described previously. [5][6][7] In our study, the majority of the cases had unilateral high myopia, whereas most reported cases of myopic convergent strabismus fixus were reported to be bilateral. 8 Regardless of age of onset, all of our patients gave recent history of progression of their deviation.…”
Section: Discussionmentioning
confidence: 47%
“…In the current study, because most of the patients had full or nearly full ocular versions, the strabismus did not qualify as myopic divergent fixus variety, as has been described previously. [5][6][7] In our study, the majority of the cases had unilateral high myopia, whereas most reported cases of myopic convergent strabismus fixus were reported to be bilateral. 8 Regardless of age of onset, all of our patients gave recent history of progression of their deviation.…”
Section: Discussionmentioning
confidence: 47%